Platform Session – Evoked potentials & NIOM: Somatosensory evoked potentials and central motor conduction times help predict outcomes from deep brain stimulation (DBS) in children with dystonia. (May 2018) - McClelland, Verity M.; Fialho, Doreen; Flexney-Briscoe, Denise; Holder, Graham; Elze, Markus; Gimeno, Hortensia; Siddiqui, Ata; Mills, Kerry; Selway, Richard; Lin, Jean-Pierre
Abstract : Introduction: DBS of the Globus pallidus internus has dramatic benefits in primary dystonia. Responsiveness of secondary dystonia is more modest and varies markedly between individuals. Predictive markers are lacking and the underlying pathophysiology of secondary dystonia is poorly understood. We report Somatosensory Evoked Potentials (SEPs) and Central Motor Conduction Times (CMCT) in children with dystonia and test the hypothesis that these parameters relate to outcome from DBS. Methods: Data were obtained from 180 consecutive children with dystonia undergoing multidisciplinary DBS assessment (mean age 10 years; range 2.5–19). Transcranial Magnetic Stimulation was applied to motor cortex and Motor Evoked Potentials were recorded in the activated contralateral hand and foot muscles. CMCT to each limb was calculated using the F-wave method. Median nerve SEPs were recorded over ipsilateral Erb's point, 7th and 2nd cervical vertebrae and contralateral centroparietal scalp. Posterior tibial nerve SEPs were recorded over ipsilateral popliteal fossa and midline centroparietal scalp. A mid-frontal reference was used. Electrical stimuli of 0.2millisecond duration were applied at 2.1 Hz, just above motor threshold. SEPs were classed as abnormal if delayed, absent or of abnormal waveform. Technically unsatisfactory recordings were excluded. Structural abnormalities were assessed with cranial MRI. Outcome from DBS at 1 year was assessed as percentage improvement in Burke-Fahn-Marsden Dystonia Rating Scale (BFMDRS-m). Results: Of the 146 children with satisfactory CMCT data, 28(19%) had an abnormal CMCT to at least one limb. Of the 100 children with satisfactory cortical SEP data, 47 had at least one abnormal cortical potential. Abnormal CMCTs and SEPs were both observed more frequently in secondary than primary/primary plus dystonia (CMCT: 22% vs. 9%, SEP: 53% vs. 24%). Of children proceeding to DBS, improvement in BFMDRS-m was greater in those with normal (n = 78) than abnormal CMCT (n = 11) (Mann Whitney p = 0.002) and in those with normal (n = 35) versus abnormal SEPs (n = 16) (Mann Whitney p = 0.001). On sub-group analysis, these relationships were preserved regardless of aetiology (primary versus secondary) or cranial imaging (normal vs abnormal MRI). Conclusion: CMCTs and SEPs provide objective evidence of motor and sensory pathway dysfunction in children with dystonia. Abnormal CMCTs and SEPs relate to DBS outcome, therefore contributing to patient selection and counselling of families about potential benefit from neuromodulation.